Internationalization of the Flagship University: Arctic Vector - Inna V. Ryzhkova; Andrei M. Sergeev (Высшее образование в России)
The article addresses complex process of internationalization in higher education which largely determines the specifics of a regional educational establishment that has the status of a flagship university. In the modern context, the internationalization of higher education serves as a strategy for active introduction of the international dimension into all the basic spheres of university life and turns out to be a much wider phenomenon than just a simple combination of various types of international activities. As a constantly evolving process, internationalization implies the continuous transformation of various educational areas and acts as a catalyst for external changes occurring in education. Despite the fact that in the basic documents regulating the functioning of flagship universities, international activities are not singled out as a separate area, the Murmansk Arctic State University (MASU) includes an international component in its strategic development program, assuming the implementation of a distributed model when the international component is consistently integrated into educational, research- and innovation-related and administrative aspects of the university’s functioning. The authors analyze the distinctiveness of the internationalization forms on the basis of such best practices implemented by the Murmansk Arctic State University as the research and educational project “Borderology”, the program “Bachelor of Northern Studies” and many others. The specific character of the region informatively and structurally determines the educational space of a flagship university, the northernmost higher education establishment of the Russian Federation, developing in a transboundary field. The authors argue convincingly that international activities significantly enhance the potential of the flagship university, allowing the use of international network resources to ensure the socio-economic development of the region and in order to enrich its socio-cultural space. The movement towards internationalization, the value positioning of the internationalization of higher education, according to the authors, mean for a modern university a kind of test of its flexibility, ability to adapt and innovate.